2015
DOI: 10.1128/aem.04269-14
|View full text |Cite
|
Sign up to set email alerts
|

A Patatin-Like Protein Associated with the Polyhydroxyalkanoate (PHA) Granules of Haloferax mediterranei Acts as an Efficient Depolymerase in the Degradation of Native PHA

Abstract: cThe key enzymes and pathways involved in polyhydroxyalkanoate (PHA) biosynthesis in haloarchaea have been identified in recent years, but the haloarchaeal enzymes for PHA degradation remain unknown. In this study, a patatin-like PHA depolymerase, PhaZh1, was determined to be located on the PHA granules in the haloarchaeon Haloferax mediterranei. PhaZh1 hydrolyzed the native PHA (nPHA) [including native polyhydroxybutyrate (nPHB) and native poly(3-hydroxybutyrateco-3-hydroxyvalerate) (nPHBV) in this study] gra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
27
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 26 publications
(27 citation statements)
references
References 50 publications
0
27
0
Order By: Relevance
“…mediteranneimediated PHA production has been further optimized by researchers all around the world. Whereas some of these groups focused on the application of inexpensive carbon feedstocks to safe substrate costs, such as whey permeate from dairy industry [12,13,48], rice-based ethanol stillage [49], extruded rice bran [50], enzymatically extruded starch [51], crude glycerol phase [28], olive mill waste water [52], vinasse [53], etc., others clarified the enzymatic and genetic background of PHA-synthesis [54][55][56][57] and in vitro degradation [58] by this organisms. Mathematic models of PHA-production [59], and kinetic studies of PHA and by-product synthesis and degradation [60] were reported for Hfx.…”
Section: Discussionmentioning
confidence: 99%
“…mediteranneimediated PHA production has been further optimized by researchers all around the world. Whereas some of these groups focused on the application of inexpensive carbon feedstocks to safe substrate costs, such as whey permeate from dairy industry [12,13,48], rice-based ethanol stillage [49], extruded rice bran [50], enzymatically extruded starch [51], crude glycerol phase [28], olive mill waste water [52], vinasse [53], etc., others clarified the enzymatic and genetic background of PHA-synthesis [54][55][56][57] and in vitro degradation [58] by this organisms. Mathematic models of PHA-production [59], and kinetic studies of PHA and by-product synthesis and degradation [60] were reported for Hfx.…”
Section: Discussionmentioning
confidence: 99%
“…Comparing to the R-ECH research in bacteria, the characterization of R-ECH in archaea was barely known until recently. Previously, six PHA-granule-associated proteins (PGAPs) 15 16 were identified in the haloarchaeon Haloferax mediterranei , a model strain for PHA metabolism research in archaea 17 18 19 . The six PGAPs include putative R-ECH (HFX_5217), phasin PhaP 15 , regulatory protein PhaR 20 , PHA synthase subunits PhaE and PhaC 21 , and PHA depolymerase PhaZh1 16 .…”
mentioning
confidence: 99%
“…The intracellular PHBV gradually degrades when the PHA-rich cells of Hfx. mediterranei are transferred into a fresh medium without carbon source [121]. Strikingly, in addition to the five PHA granule associated proteins, two new proteins were observed on the PHA granules in this strain.…”
Section: Pha Mobilization and Degradationmentioning
confidence: 84%
“…Interestingly, the expression level of phaRP was enhanced in the presence of PHA as the activity of the phaRP promoter decreased by twofolds in the ΔphaEC and ΔphaPEC mutants of Hfx. mediterranei [121]. However, knocking out of the phaR gene increased the activity of the phaRP promoter by fourfolds in the ΔphaRPEC mutant, indicating that PhaR is a negative regulator of the phaRP operon [118].…”
Section: Regulation Of Pha Synthesismentioning
confidence: 98%
See 1 more Smart Citation